The psychometric properties of the Varieties of Inner Speech Questionnaire-Revised in Hebrew - Sabag, Tal; Zohar, Ada H.; Kreiner, Hamutal; Lev-Ari, Lilac; Rabinowitz, Dean (Frontiers in Psychology, 2023)
The Varieties of Inner Speech Questionnaire-Revised (VISQ-R) is a self-report questionnaire designed to measure characteristics of inner speech. In the current study, we adapted and validated a Hebrew version of VISQ-R. Our first hypothesis was that Confirmatory Factor Analysis (CFA) of the Hebrew VISQ-R would confirm the five subscales replicating the factor structure of the original questionnaire. In addition, building on previous findings that inner speech is involved in tasks that require the executive functions we examined the relationship between VISQ-R and self-reported executive functions questionnaire (BRIEF-A). We hypothesized that correlations between subscales of the Hebrew VISQ-R would reveal covariance between BRIEF-A and some but not all inner speech subscales. 406 participants completed the Hebrew VISQ-R and 280 of them also completed the BRIEF-A. As hypothesized, CFA confirmed the factor structure revealing the same 5 subscales reported in the original English version, with acceptable internal reliability. Partial support was found for the hypothesized correlations between VISQ-R and BRIEF-A, with covariance of executive functions with some subscales of inner speech (Evaluative, Other-People and Dialogic), and distinct variance with others (Condensed and Positive). These results indicate that the Hebrew version of the VISQ-R has good psychometric properties and that it can be used in future research. The implications concerning the contribution of inner speech for people with difficulties in executive functions are discussed.